Emotional Intelligence, Work/Family Conflict, and Work Values among Customer Service Representatives: Basis for Organizational Support - Sergio, Rommel P.; Gonzales-Lim Ormita, Luzelle Anne; Dungca, Antonette Lazaro; Ocampo-Gonzales, Jennifer (Journal of Eastern European and Central Asian Research (JEECAR), 2015)
This research paper discusses the profile of emotional intelligence, work/family conflict, and work values among 437 purposively selected customer service representatives (CSRs) from the Middle East, Iran, Pakistan, Russia, India, and the Philippines. Moreover, the study leads to a set of organizational change development programs to assist organizations to cope with their diversity concerns. The descriptive, comparative-correlational methods were employed as this paper also aims to find the correlates of emotional intelligence such as work/family conflict, and work values. The researchers utilized several instruments, namely the Demographic Profile Sheet, Emotional Competence Inventory, Work/Family Conflict Scale, and Work Values Inventory. The general findings reveal that there is a significant relationship between emotional intelligence and work/family conflict, particularly on the areas of self- management, social awareness and relationship management; whereas, there is a significant relationship between emotional intelligence (particularly on the clusters of self- management, social awareness and relationship management) and work values (specifically in the areas of management, achievement, supervisory relations, way of life, and independence). The organizational development support programs with emphasis on diversity management have been recommended to set future directions for call center organizations involved in the study.